Penanaman Nilai-Nilai Karakter dengan Pendekatan Student Centered Learning pada MKWU-PAI di Perguruan Tinggi Umum - Iwan Hermawan; Nok Nasibah; Uus Ruswandi; Bambang Samsul Arifin (Edumaspul: Jurnal Pendidikan, 2021)
Education is not just about the learning process for knowledge, understanding, and skills, but the substance of education is to shape human character with good values ​​that come from norms, ethics, customs, and religions. By referring to the five pillars of character found in strengthening character education in Indonesia, the inculcation of character values ​​in the education process requires an appropriate, appropriate, and effective learning model approach. One of the learning model approaches to instill character values ​​is the student-centered learning model approach or learning model that provides flexibility for students to be active, creative, innovative, inspirational, interactive, independent, collaborative, cooperative, and contextual. There is harmony between the student-centered learning approach and character education because both instill and foster good character values. The methods used to support the learning process referred to are discussion, problem-based, and project-based methods. Based on that, this research is a development (research and development) that starts from the process of developing, collaborating, and perfecting the learning model between the values ​​of strengthening character education and the student-centered learning approach at MKWU-PAI in Public Universities.